2013
DOI: 10.1016/j.arr.2012.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of somatoform disorders and medically unexplained symptoms in old age populations in comparison with younger age groups: A systematic review

Abstract: Prevalence of somatoform disorders and medically unexplained symptoms in old age populations in comparison with younger age groups Hilderink, P. H.; Collard, R.; Rosmalen, Judith; Oude Voshaar, Richard C. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(79 citation statements)
references
References 50 publications
4
69
2
4
Order By: Relevance
“…Accordingly, SHS sufferers are typified by impaired quality of life, frequent hospital visits and incurred medical expenses [20,21]. A previous investigation by the current authors found that suboptimal health status was applicable to 65.1% of the surveyed population in Southern China [24], with SHS now a major global public health challenge [20,25,26]. Current prevention and intervention strategies recommend disease prevention and effective treatment of early-stage illness [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, SHS sufferers are typified by impaired quality of life, frequent hospital visits and incurred medical expenses [20,21]. A previous investigation by the current authors found that suboptimal health status was applicable to 65.1% of the surveyed population in Southern China [24], with SHS now a major global public health challenge [20,25,26]. Current prevention and intervention strategies recommend disease prevention and effective treatment of early-stage illness [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…47 MUS are quite common in later life; however, the available data suggest that the prevalence rate declines after the age of 65 years. 48 These apparently contradictory results might be due to the lack of a consensus in the definition of MUS, which fall into the category of somatomorphic disorders, as well as the paucity of guidelines of MUS definition and management. 49 Estimates of prevalence inevitably vary with definition, but are higher in patients seen at primary care doctor's offices, with these physicians having more confidence in their ability to diagnose and manage mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Important population based studies that have investigated the prevalence of mental disorders define the age of 65 years as a cutoff and thereby exclude the elderly population [3][4][5][6] or somatoform disorders are excluded a priori in studies exploring mental disorders in the elderly [7]. Some attention has already been paid to the neglect of somatoform disorders by geriatric psychiatry [8], yet the reviews dealing with this issue all come to similar conclusions: empirical data are scarce, and results are highly heterogeneous, as 12 month prevalence rates vary from 0.0% to 30.1% [9][10][11].…”
Section: Introductionmentioning
confidence: 91%
“…As mentioned previously, studies investigating somatoform disorders in the elderly are rare, and the reported prevalence rates are highly heterogeneous [9,11]. One reason for this heterogeneity might lie in the controversial conceptualization of this group of disorders.…”
Section: Prevalence Of Somatoform Disorders In the Elderly-why We Shomentioning
confidence: 99%
See 1 more Smart Citation